The repetition process in Sarraute's dramatic works, the verbal language's dynamics or its stagnation? - Mahdi Afkhaminia; Allahshokr Assadollahi; Naimeh Karimlou (زبان پژوهی, 2020)
Repetition can be considered as one of the expressions of Nathalie Sarraute's tropism in the external language. The language of Sarraute reflects the sensation more than the meaning. Even if the perception, understanding, and certain explanation of this language excited by the sensation seem to be impossible, the marks of this shaking are manifested in verbal forms such as repetition. The study of repetition is important because it is used extensively in Sarraute's text and plays a crucial role in increasing verbal communication. In the novels of Nathalie Sarraute, the narrator's agitated language is a good place for the appearance of tropism, while in dramatic works, the erased narration is replaced by the short and few blocking and this is how the importance of speech increases. The role of repetition in dynamism of the text and its relation to tropism are the elements that will be emphasized in this research. Figures of insistence or repetition such as anaphora, redundancy, polysyndeton or simple repetition make the narrative progress temporary, while they make the sentences syntactically entangled. Translating monotonously and uniformly, they have the ability to convey the effect of interest and indignation at the same time to the reader. Consistent with the sensation but opposed to the reason, they bring to the text the mark of tropism. Alongside the figures of interruptions and omissions that attenuate the progress of speech, the emphasis figures prolong verbal communication through repetitions and the process of word reproduction. All these figures, widely used in Sarraute's works, represent in fact the anomalies or the verbal disorders coming from the resistance of the interior language to the exteriorization. Françoise Calin studied "reiterations" in Nathalie Sarraute's novels, especially from the narrative points of view. He gave some examples in which a single conversation is sometimes repeated by different speakers that resulted in the "stagnation of the story". We take this expression of Calin to show the effect of repetition in the dramatic texts of Sarraute. The figures of repetition, redundancy and polysyndeton are one of the main anomalies causing the entanglement of structures of the text and its stagnation. But in this stagnation, there is a kind of dynamism and it is considered as one of the solutions of the momentary recording of tropism. According to Sarah Anthony's explication in "Between the Spoken and the Unspoken: a Sarrautian Dialectic," Sarraute uses repetitions to dilate the tropism. Anthony summarizing parts of the book The said and the unsaid in Nathalie Sarraute's The Use of Speech written in 2006 by Sarah Charieyras, expresses the difficulties of grasping and understanding the tropisms. She explains the problem of the inexpressible and the brevity of the tropismic movements in her work. According to her, "Sarraute dilates the text to expose the minutiae of tropisms to the readers." Repetition is then a linguistic instrument not to restrain, but at least to slow down the distracted flight of tropism in order to exhibit these implicit movements of the inner language by the explicit structures of verbal language. In this article, we will examine these verbal excitements caused by repetitions, and whether they advance Sarraute's text or reduce his advancement. The considerable use of repetition is not an arbitrary choice. The author uses it to distort the structures of speech and to give them a deregulated and rebellious figure. The speech carriers (characters) of Sarraute's language do not seem normal to reveal the power of a troubled language that is full of expression, which forces the man to manifest and express himself. Since the universe of expressible and perceptible facts is smaller than that of the inexpressible and imperceptible facts, inevitably the externalized language carries traces of irrationality. Sarraute's language is in the general sense of the term the executioner and the victim at the same time. Obliged to externalize himself to begin to exist, he loses his originality at the expense of existing verbally, but it is a perpetually destructive birth that pushes the utterance to die out and throws a challenge to his carrier. Repetition seems more specific when it becomes a solution and a language practice among the characters to maintain contact as much as possible. However, they resign themselves inevitably to repetition figures in order not to lose the least communicational chances. It is an uncomfortable and painful choice for the sarrautian porters who, in the philosophical sense of the word, already consider "to speak" as a "copy of copy". Repetitive words most often play the role of triggers for tropism. They seem to be the free choices of speech carriers who, in an instant, delay the ordinary progress of the text.